Sistem Informasi Simpan Pinjam Dana Gapoktan Pada Desa Pematang Panjang Berbasis Desktop : - - darmono, darmono (CV. Multi Kreasi Media, 2023)
− Gapoktan Cooperative is a community organization engaged in the economic sector as a cooperative business entity in Pematang Panjang village, East Seruyan Hilir sub-district, Seruyan district, central Kalimantan. Data processing at the Gapoktan collective in Pematang Panjang Village is still carried out using Ms. Excel and Ms. Word applications in recording member data, searching member data, loans, and member deposits. This is an obstacle for cooperative officers, resulting in the length of service to its members. So the need to build a desktop-based information system for saving and borrowing Gapoktan funds that can solve the problems faced by the Pematang Panjang village Gapoktan cooperative because recording and searching data can be done quickly. So that errors or mistakes that have occurred so far can be minimized. In making application programs using software (software) Borland Delphi 7 as a programming language and using Interbase software as a database.